2022
DOI: 10.1093/infdis/jiac101
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF1B and TNF Variants Are Associated With Differences in Levels of Soluble Tumor Necrosis Factor Receptors in Patients With Severe COVID-19

Abstract: Background The impact of genetic variants in the expression of TNF-α and its receptors in COVID-19 severity has not been previously explored. We evaluated the association of TNF (rs1800629 and rs361525), TNFRSF1A (rs767455 and rs1800693), and TNFRSF1B (rs1061622 and rs3397) variants with COVID-19 severity, assessed as invasive mechanical ventilation (IMV) requirement, and the plasma levels of soluble TNF-α, TNFR1, and TNFR2 in patients with severe COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…24 Galindo et al also studied TNF (rs1800629 and rs361525), TNFRSF1A (rs767455 and rs1800693), TNFRSF1B (rs1061622 and rs3397) polymorphisms and they reported that TNF and TNFRSFB1 gene polymorphisms affect the plasma levels of soluble TNFR1 and TNFR2, which are implicated in COVID-19 severity. 29 TNF- inhibitors may be an effective therapy for preventing disease progression in severe SARS-CoV-2 infection, and therefore, determining associations between TNF gene polymorphisms and disease severity will be helpful for the selection of candidates who may benefit from anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Galindo et al also studied TNF (rs1800629 and rs361525), TNFRSF1A (rs767455 and rs1800693), TNFRSF1B (rs1061622 and rs3397) polymorphisms and they reported that TNF and TNFRSFB1 gene polymorphisms affect the plasma levels of soluble TNFR1 and TNFR2, which are implicated in COVID-19 severity. 29 TNF- inhibitors may be an effective therapy for preventing disease progression in severe SARS-CoV-2 infection, and therefore, determining associations between TNF gene polymorphisms and disease severity will be helpful for the selection of candidates who may benefit from anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies investigating relationships between genetic variations and the clinical course of COVID-19, only certain genes and certain sequences have been investigated [18][19][20] and there are inconsistencies between the results of these studies. [25][26][27][28][29] Moreover, there are a few Turkish studies on previously published gene polymorphisms that have assessed relationships between COVID-19 and genetic factors. 26,30,31 So hopefully, this study will increase evidence regarding the relationships between gene variants and disease severity, by adding novel variants through the sequencing of three primary genes associated with COVID-19, namely ACE, IFNG, and TNF-a.…”
Section: Introductionmentioning
confidence: 99%
“…In COVID-19 patients, elevated levels of TNF-R1 and TNF-R2 have been detected. 28 In addition, levels of soluble TNF-R1 were correlated with the severity of the disease. 29 Like microbial infections, other xenobiotics could also be detrimental to the health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the TNF rs909253 allele has been significantly more common in COVID‐19 patients than in the control population 53 . In a recent study, TNFRSF1B rs3397 or TT genotype was associated with lower Horowitz index (PaO 2 /FiO 2 ratio) compared to CT + CC genotypes being related to different TNFR1 and TNFR2 levels 54 …”
Section: Tnf Gene Polymorphismsmentioning
confidence: 98%
“… 53 In a recent study, TNFRSF1B rs3397 or TT genotype was associated with lower Horowitz index (PaO 2 /FiO 2 ratio) compared to CT + CC genotypes being related to different TNFR1 and TNFR2 levels. 54 …”
Section: Tnf Gene Polymorphismsmentioning
confidence: 99%